The question of the admissibility of the application of the polygraph in the course of proof within the criminal case - Bryanskaya, Elena V.; Samaryn, Vadzim I. (Journal of the Belarusian State University. Law, 2019)
One of the stages of proving within a criminal case is the collection of evidence, which consists in the formation of evidence, that is, in the transformation of non-procedural information into a procedural one. However, before giving the information not just procedural, but evidentiary value, we must examine it, must give a substantive part to the analysis. Since the participants in criminal proceedings have some information that allows to find the circumstances of a committed crime during analyzing specific cases from judicial practice, it became obvious to us that such participants can intentionally distort information in pursuit of their interest. In this regard, the criminal investigative authorities could use a polygraph in establishing the truth or falsity of the testimony. However, not all law enforcers definitely express on the advisability of using a polygraph and the commission of a psycho-physiological expert evaluation, there are conclusions about the doubtfulness of such an expert’s opinion, that allows us to suggest its inadmissibility as evidence in the criminal case.